KS0 and Λ0 production studies in pp̄ collisions at s=1800 and 630 GeV - Acosta, D; Affolder, T; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Ashmanskas, W; Azfar, F; et al. (2005)
We present a study of the production of KS0 and Λ0 in inelastic pp̄ collisions at s=1800 and 630 GeV using data collected by the CDF experiment at the Fermilab Tevatron. Analyses of KS0 and Λ0 multiplicity and transverse momentum distributions, as well as of the dependencies of the average number and pT of KS0 and Λ0 on charged particle multiplicity, are reported. Systematic comparisons are performed for the full sample of inelastic collisions, and for the low and high momentum transfer subsamples, at the two energies. The pT distributions extend above 8GeV/c, showing a pT higher than previous measurements. The dependence of the mean KS0(Λ0) pT on the charged particle multiplicity for the three samples shows a behavior analogous to that of charged primary tracks. © 2005 The American Physical Society.